Novel combination therapy to target heart and kidney - S. Lekawanvijit (2018)
© Springer International Publishing Switzerland 2015. Due to a significant burden of the common coexistence of chronic kidney disease (CKD) and cardiovascular disease (CVD) as well as their complex pathophysiological interplay, the concept of integrated cardiorenal pathology has been increasingly recognized. A continuing increase in prevalence of CKD has become a global health concern. One of the major consequences of the growing CKD population is a further deterioration of the CVD epidemic. CKD patients are at extraordinarily high risk for CVD; and CVD in turn is the single most common cause of death in the CKD population, especially in the dialysis-dependent subgroup. Interestingly, traditional cardiovascular risk factors are not sufficient to explain the high prevalence of CVD in this population. There have thus been major efforts in search of novel risk factors specific or closely-related to the CKD milieu. Evidence of non-dialyzable protein-bound uremic toxins as potential risk factors for CKD-associated cardiovascular pathology and mortality as well as potential strategies targeting these toxins has emerged in recent years. At present, indoxyl sulfate and p-cresyl sulfate are the two most problematic toxins with regard to their negative cardiorenal impact. Along with ongoing development in dialysis technique to improve removal of these toxins, novel therapies that reduce the production of such toxins offer a potential approach to alleviating, or even preventing, their toxic effects on heart and kidney.